Studi Fenomenologi Pengalaman Penderita HIV dan AIDS Tanpa Pasangan Hidup dalam Memenuhi Kebutuhan Seksual di Lembaga Kasih Indonesia Tahun 2013 - Salamah Thomasita Batubara; Maisaroh Maisaroh (Jurnal Soshum Insentif, 2020)
STUDY ON HIV AND AIDS PATIENTS WHO LIVE AS A SINGLE IN FULFILLING THE SEXUAL NEEDS AS RECORDED IN 2013 BY LEMBAGA KASIH INDONESIA This phenomenology study analyzes the experiences of HIV and AIDS patients who live as a single in fulfilling the sexual needs. The analytical tool used is the phenomenology design. Data sampling is derived from in-depth interviews, and the verbatim result is revealed through the Colaizzi methodology. Subjects of the study focus on past incidents that caused the HIV infection, emotional experience after infection, personal observation when sexual needs arise, ways to fulfill the related needs, common obstructions in the process of fulfillment, and the expectations of HIV and AIDS patients who live as a single. To fulfill the sexual needs, the HIV and AIDS patients who live as a single refer to two different options, which are having sexual intercourse with condom and masturbation. This study recommends the necessity of condom in the sexual intercourse for HIV and AIDS patients.